2010
DOI: 10.1210/jc.2009-1389
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Growth Hormone Therapy Changes the Natural History of Body Composition and Motor Function in Children with Prader-Willi Syndrome

Abstract: hGH treatment in children with PWS, begun prior to 2 yr of age, improves body composition, motor function, height, and lipid profiles. The magnitude of these effects suggests that long-term hGH therapy favorably alters the natural history of PWS to an extent that exceeds risks and justifies consideration for initiation during infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(141 citation statements)
references
References 18 publications
7
129
2
3
Order By: Relevance
“…Most individuals with PWS, but not all, are deficient in GH and studies that were initially focused on improving growth have not only demonstrated this effect, but also improvements in metabolism, body composition, behavior and cognition (38)(39)(40)(41)(42)(43)(44). However, GH therapy on occasion can be associated with significant side effects, such as the stimulation of adenoid tissue leading to obstructive sleep apnea so it should be used carefully in the treatment of PWS.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…Most individuals with PWS, but not all, are deficient in GH and studies that were initially focused on improving growth have not only demonstrated this effect, but also improvements in metabolism, body composition, behavior and cognition (38)(39)(40)(41)(42)(43)(44). However, GH therapy on occasion can be associated with significant side effects, such as the stimulation of adenoid tissue leading to obstructive sleep apnea so it should be used carefully in the treatment of PWS.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…39 Some studies reported that GH increases LBM (mainly determined by muscle mass) [20][21][22]26,29 ; however, in these studies, the interpretation of the reported results is problematic because the increase in LBM was not corrected for changes in height. Studies in children with PWS that reported height-corrected LBM have found that LBM normally decreases over time, but with GH treatment LBM stabilizes.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 ,20 In children with PWS, GH treatment has a positive effect on agility and thoracic muscle strength. 21,26,29,30 To relate decreased muscle thickness in PWS to muscle weakness and motor developmental delay, it would be interesting to use a more direct measure of specific muscle groups and compare this with strength measurement to determine the direct relationship between structure and function.…”
mentioning
confidence: 99%
“…In the case of children with PWS, GH therapy can improve growth, body composition, muscle thickness, physical strength and agility, motor performance, fat utilization, and lipid metabolism [184][185][186]. The best response to GH in PWS patients is observed in the first 12 months of treatment.…”
Section: Treatment Options In Patients With Genetic Obesitymentioning
confidence: 99%